HIMENOPTEROS PARASITOIDES DE LOS GENEROS ADITROCHUS RUEBSAAMEN Y ESPINOSA GAHAN (INSECTA, HYMENOPTERA, PTEROMALIDAE) ASOCIADOS A AGALLAS EN NOTHOFAGUS (FAGACEAE) DEL SUR DE ARGENTINA Y CHILE - De Santis, Luis; Fidalgo, Patricio; Ovruski, Sergio (Acta Entomológica Chilena, 2022)
The authors first describe four new species of Aditrochus, two from Chile (bouceki and chilensis) and two from Argentina (coihuensis and gnirensis). A. coihuensis was obtained from galls on Nothofagus dombeyi and A. gnirensis from galls on N. antárctica. The species A. fagicolus Ruebsaamen, 1902 obtained from galls on N. pumilio is redescribed. A key for the five species of Aditrochus here studied is provided. It is also given information about a new species of Espinosa from galls on N. obliqua in Argentina. E. nothofagi Gahan, a chilean species, is registered for the first time in Argentina; this species was obtained from two different galls on N. obliqua and N. alpina respectively. Some important morphological characters of the genera Espinosa and Aditrochus and the galls from wich they were obtained are illustrated.